Ciência-tecnologia-sociedade : suas interrelações e seu ensino nas concepções de licenciando em química - Santos, Rafaela Cristina da Silva (2017)
The present research seeks to analyze the conceptions about CTS (Science-Technology-Society) and about the teaching in this perspective, of graduates in Chemistry of an IES of the state of Sergipe (Institutions of Higher Education) of the private network (Association of Education and Culture Pio Tenth), relating such conceptions to relevant aspects of their initial formation. This IES is located in the city of Aracaju, located in the state of Sergipe.. The research was developed through a qualitative approach. For this, the data collection was divided in three moments. In the first collection, there was the analysis of the curricular matrix of the course of Degree in Chemistry offered by the IES. This analysis was not an in-depth analysis, since the objective of this stage was to analyze the existence or not of subjects that contemplate the CTS conceptions, as well as to analyze the philosophical line that this curricular matrix seeks to follow. Type of state of the art, that sought to select works that already exist in the academic environment that approach or resemble the subject of the research. In the second stage of the research, an investigative questionnaire was applied, consisting of two parts: the first one was the application of the Portuguese version abbreviated by Canavarro (1999) containing 14 questions from the VOSTS (Views on Science-Technology-Society) questionnaire. The second part of the questionnaire was composed of 06 open questions about C-T-S teaching and the initial training of subjects related to this teaching paradigm. In the third moment of the data collection, there was the application of a focal group with 06 of the 07 subjects of the research. For the analysis of the data collected through the VOSTS questionnaire, a categorization of the responses was chosen considering the categories that were established by Canavarro (1999) in his adapted version of the VOSTS questionnaire. For the analysis of the second stage of the questionnaire and the data collected through the focus group, we used the Discursive Textual Analysis, proposed by Moraes and Galiazzi (2011). The results obtained in the research allow to show that the CTS conceptions that the subjects possess, in their majority, are in agreement with the already defined categories in the literature as realistic and acceptable on Science and Technology and its influences in the Society. Therefore, the members of the research have CTS conceptions acceptable to their formation.